2017
DOI: 10.5435/jaaosglobal-d-17-00032
|View full text |Cite
|
Sign up to set email alerts
|

Is It Time We Changed How We Measure Length of Stay for Hip and Knee Arthroplasty?

Abstract: Introduction:Patient length of stay (LOS) for lower limb arthroplasty is a frequently quoted outcome measure. However, the use of mean values in days is prone to being skewed by outliers.Methods:Between January 2013 and December 2015, patient LOS for primary hip and knee replacement was collected in 1,168 patients. There were two groups: pre- and postinstitution of the Rapid Recovery Program. The hypothesis was that reducing LOS would highlight proportionate differences when using hours as the measuring unit.R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 13 publications
(11 reference statements)
1
20
0
Order By: Relevance
“…In Professor Pearce’s team’s writing on rapid recovery, it states that ‘mobilisation of patients is predominantly performed by physiotherapists and, to a lesser extent, the ward nurses’. 11 However, we have seen a paradigm shift in this where nursing staff have taken on responsibility for early mobilisation with impact. Due to the technique being embraced by nursing staff and the improved equipment made available, in the most recent 3 months of data all patients were mobilised on day 0.…”
Section: Resultsmentioning
confidence: 99%
“…In Professor Pearce’s team’s writing on rapid recovery, it states that ‘mobilisation of patients is predominantly performed by physiotherapists and, to a lesser extent, the ward nurses’. 11 However, we have seen a paradigm shift in this where nursing staff have taken on responsibility for early mobilisation with impact. Due to the technique being embraced by nursing staff and the improved equipment made available, in the most recent 3 months of data all patients were mobilised on day 0.…”
Section: Resultsmentioning
confidence: 99%
“…Outpatient total joint arthroplasties can be implemented safely, cost-effectively and are beneficial to patients. Increased LOS is associated with higher morbidity and mortality (Lazic et al 2018;McCulloch et al 2017). In SA, outpatient arthroplasty surgeries have not yet been performed.…”
Section: Introductionmentioning
confidence: 99%
“…Early mobilisation (patient ambulating or walking with an appropriate mobility aid away from the bed), plays an essential role in decreasing post-operative complications, including deep vein thrombosis (DVT), prosthesis-related infections and postural hypotension (Chen et al 2012;Dossett & Chesser 2017). Physiotherapy intervention also improves patients' function and muscle strength (Chen et al 2012;McCulloch et al 2017). When considering outcomes after total knee arthroplasty, Kolisek et al (2009) reported that joint range of motion (ROM) and function were comparable with the final follow-up for both patients having surgery out-and inhospital.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the average length of hospital stay after artificial joint replacement has decreased [2]. Modern artificial joint replacement technology allows surgical patients to be safely discharged within a short period of time after surgery [3,4].This trend of shorter length of hospital stay emphasizes the importance of pre-discharge patient education. A large proportion of postoperative adverse events may be avoided and can be prevented by better patient education and enhanced postoperative counseling [5].…”
Section: Introductionmentioning
confidence: 99%